Hierarchical Bi2MoO6 nanosheet-built frameworks with excellent photocatalytic properties. Issue 30 (18th March 2015) - Ma, Ying; Jia, Yulong; Jiao, Zhengbo; Yang, Min; Qi, Yanxing; Bi, Yingpu
Abstract : We demonstrate a simple and effective strategy for rationally fabricating one-dimensional (1D) Bi2 MoO6 nanosheet-built frameworks, which exhibit much higher photocatalytic performances than conventional Bi2 MoO6 nanoplates and nanoparticles for the degradation of organic contaminants under visible light irradiation. Abstract : Herein, we demonstrate for the first time the fabrication of one-dimensional (1D) Bi2 MoO6 inter-crossed nanosheet-built frameworks by using MoO3 nanobelts as the growth templates and molybdate source. Especially, this novel Bi2 MoO6 framework structure exhibits remarkably enhanced photocatalytic activity toward the degradation of organic dyes under visible-light irradiation, far exceeding that of conventional Bi2 MoO6 nanoplates and nanoparticles. The photoelectrochemical study suggests that the hierarchical framework structure could facilitate the photoinduced charge separation and transfer from the inter-crossed Bi2 MoO6 nanosheets, which may make a significant contribution to the enhanced photocatalytic activity.